STUDY OF PREPARATION OF FINANCIAL STATEMENTS IN ACCORDANCE IN ACCORDANCEWITH GOVERNMENT REGULATION NO. 24 YEAR 2005 ON SAP (CASE STUDY ON CITY GOVERNMENT SOLOK) - Darmadi, Cherie (Accounting, 2010)
Good governance is a demand in the people and the nation. The Indonesian nation as part of the world community has an obligation to participate in realizing good governance (good governance). Good governance, among others, characterized by the existence of an accountable and transparent government. To achieve a transparent and accountable governance in accordance with the principles of good governance in the financial management of the State. The Government has issued Government Regulation No.. 24 year 2005 regarding Government Accounting Standards (SAP) which is the accounting principles applied in preparing and presenting financial statements of government The uniformity of format and structure of financial statement presentation allows tertutupinya relevant information and the local specialty, for financial recording and reporting challenge is different between one period to the next period, especially with the multitask nature of public services and require rapid treatment. While presenting the Budget and Balance Sheet Actual report by the City of Solok during the Year 2005 and 2006 are still based on Kepmendagri No.. 29 year 2002, while SAP was implemented in the presentation of Budget Realization Report and Balance Sheet in 2007 and 2008. This demonstrates the Government of the City of Solok not ready to comply with Regulation No.. 24 of 2005 that the financial statements shall be prepared and presented by SAP. Government Performance during 2005-2008 City of Solok Solok City Government capability in performing their duties very effectively with an average of 105.67%. Solok City Government can be said to be very efficient in doing polling PAD with an average of 37.7% shows the number. The overall rate of absorption of funds by the City Government is good Solok. From this condition shows that cost awareness (awareness of public money) is very good Solok City Government. During FY 2005-2008 to finance the activities undertaken Solok City Government relies on the central government since independence is an average of 9.48%. Harmony Solok City recurrent budget with construction spending quite balanced, because it dominates the direct spending by an average of 122.72% harmony. From this condition indicates that a mechanismoriented financial planning cost awareness (awareness of public money) from Solok City Government. Keywords: SAP, PAD, Budgets, Financial Reports